Evaluation of a Newly Developed LC-MS/MS Vitamin D Assay - Santiago, Jon Jon; Mitchell, Ryan W; Hunt, Waylon; Tappia, Paramjit S; Scantlebury, Dawn C; Ramjiawan, Bram (Scripta Medica, 2025)
Background/Aim: Globally, deficiency of vitamin D is highly prevalent. Besides the known consequences of vitamin D deficiency to bone health, there is now strong evidence that links low vitamin D status to an increase in the risk for diabetes, cancer, cardiovascular disease and autoimmune diseases. It is therefore important to have a highly accurate, reproducible and cost-effective test that is highly predictive of vitamin D status and of diagnostic value. This study was undertaken to validate newly developed high throughput LC-MS/MS 25-hydroxy vitamin D (25(OH)D) assay against current gold standard assays measured at two independent reference laboratories. Methods: The initial study (n = 40) and follow up study (n = 40) recruited healthy adult men and women volunteers (18 to 55 years old). Vitamin D (25(OH)D) was measured using a targeted LC−MS/MS method. Results: Unexpectedly, data were not consistent with the values for 25(OH)D obtained from the two independent reference laboratories (as evidenced by correlation coefficients and Bland Altman analyses), although the results between the two reference laboratories were in agreement and highly correlated. Conclusion: These findings highlight the continued efforts and needs for harmonisation of results and standardisation of analytical methods for 25(OH)D for diagnostic accuracy.